Biomarkers of tubulointerstitial damage and function in type 1 diabetes. Issue 1 (14th November 2017) - de Boer, Ian H; Gao, Xiaoyu; Bebu, Ionut; Hoofnagle, Andrew N; Lachin, John M; Paterson, Andrew; Perkins, Bruce A; Saenger, Amy K; Steffes, Michael W; Zinman, Bernard; Molitch, Mark E
Abstract : Objective: To evaluate biomarkers of renal tubulointerstitial damage and function in type 1 diabetes with and without diabetic kidney disease. Research design and methods: Cross-sectional case-control study of Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Study participants. Cases (N=43) had incident persistent estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 with urinary albumin excretion > 300 mg/24 hour. Controls (N=43) had persistent eGFR > 90 mL/min/1.73 m 2 and urinary albumin excretion <30 mg/24 hour. Urinary and plasma biomarkers reflecting tubular injury, inflammation, fibrosis, secretion, and synthetic function were measured from stored specimens collected at the first study visit with reduced eGFR (for case participants) or the corresponding study year (for control participants). Results: Mean (SD) age was 51 (9) and 50 (8) years for case and control participants, and mean (SD) duration of diabetes was 30 (6) and 30 (5) years, respectively. Mean (SD) eGFR was 39 (14) and 103 (9) mL/min/1.73 m 2 for case and control participants, and mean (SD) albumin excretion rate was 1978 (2914) and 10 (7) mg/day, respectively. Comparing cases with controls, significant differences were observed in each measured biomarker, including urine epidermal growth factor (mean 5.3 vs 21.2 μg/g creatinine for case vs control participants, respectively), urine monocyte chemoattractant protein-1 (596 vs 123 ng/g creatinine), urine galectin-3 (168 vs 52 μg/g creatinine), plasma soluble tubular necrosis factor receptor-1 (3695 vs 1022 pg/mL), plasma galectin-3 (21.3 vs 11.0 ng/mL), urinary clearances of hippurate (70 vs 167 mL/min) and cinnamoylglycine (77 vs 317 mL/min), and plasma arginine-citrulline ratio (5.6 vs 7.7 μg/μg), each P<0.001. Conclusions: Marked abnormalities in biomarkers of kidney tubular injury, inflammation, fibrosis, secretion, and synthetic function accompany reduced eGFR and albuminuria in type 1 diabetes. Trial registration number: NCT00360893, NCT00360815 .